Assessment of acute kidney injury in rhabdomyolytic mice by transcutaneous measurement of sinistrin excretion - Moggio, Aldo; Sticht, Carsten; Gretz, Norbert (Nephrology, dialysis, transplantation, 2017)
Background. Early and accurate assessment of renal function is required for the successful detection and treatment of acute kidney injury (AKI). However, only retention parameters such as plasma urea and creatinine, and the indirect estimation of glomerular filtration rate are commonly available. Methods. Here, we measured the kinetics of plasma fluorescein isothiocyanate (FITC)-sinistrin excretion to detect alterations of renal function over time in a murine model of rhabdomyolysis-induced AKI. The half-life of FITC-sinistrin was evaluated using a transcutaneous device at different time points in conscious mice, from 4 days before renal damage up to 30 days after. Retention markers were also evaluated, in parallel. Results. Evaluation of the FITC-sinistrin half-life revealed early reduction of renal filtration, observed as early as 6 h after renal damage, and maintained up to 12 h following AKI. Plasma creatinine and urea levels correlated with the transcutaneous measurements of sinistrin excretion. Evaluation of sinistrin excretion also demonstrated that glycerol-treated animals did not develop AKI. Finally, histological analysis showed the presence of renal parenchymal lesions, which developed following the reduced renal filtration and persisted over time, highlighting the causative role of vascular dysfunction and myoglobin toxicity on the subsequent induction of tissue damage. Conclusions. Taken together, the results of this study provide important insights into the pathophysiology of kidney injury in rhabdomyolytic mice, and indicate that the transcutaneous measurement of FITC-sinistrin is an efficient and simple method to assess renal function precisely. This method also allows reduction of the required number of experimental animals by monitoring the same mouse over time.